The mechanism of thermal oxide film formation on low Cr martensitic stainless steel and its behavior in fluoride-based pickling solution in conversion treatment. (1st April 2021) - Nabizadeh, Mohaddese; Boissy, Clément; Baert, Kitty; Goderis, Steven; Ottevaere, Heidi; Terryn, Herman; Hauffman, Tom
Highlights: The composition and the structure of the thermal oxide film on low Cr martensitic stainless steel were thoroughly studied. A set of surface analytical techniques were used to propose an oxidation mechanism for this low Cr stainless steel at high temperate. The results showed that the thermodynamic and kinetic of high temperature oxidation lead to the formation of a complex Fe-Cr oxide film covering the surface and hematite islands on top of it. The impact of fluoride ions on the thermal oxide film was studied as a pickling agent in automotive conversion treatment. The observation showed that only the Fe oxide present in the oxide film dissolves in the pickling solution through a surface complexation mechanism. Abstract: (Attention for corrosion science, the abstract must not exceed more than 100 words) In this research, first a multi-analytical approach was carried out to propose a mechanistic model for the formation of the thermal oxide film on low Cr stainless steel. It describes the effects of kinetically and thermodynamically driven phenomena on the growth of a Fe-Cr complex oxide film at 950℃. Second, the behavior of the thermal oxide film in the presence of fluoride ions, as a relevant pickling agent in conversion treatment, was investigated. It was shown that fluoride ions enter the oxide film and form a complex with Fe and preferentially dissolve hematite islands through a complexation mechanism.